(3eNJUQ GdEbJVGHs - (3SYjO Hf CHj GdNjQ Hf YjSi GdMVjQj GdfSWhQj, CHh fUQ, GdeYQha HGHf GdeSjMj,J (B658 (3g` s ((3jhMfG GdWHjH Hf ejNGFjd GdWHjH Hf YWGjG s)
(3ChdgG (B:s
(3bGd (B: (3eG MO GdWH hce CLRGDg ? GdWH Yde jYQa efg CMhGd HOf GdEfSGf ef LgI eG jUM hjRhd Yf GdUMI s
(3BNQgG (B:s
(3hgPG BNQ GdeSGFd GdWHjI GdeTJedI Ydi Led ef Yde GdWH bUO efgG dJchf eONdkG ddeHJOF hJPcQI ddefJgi hai Pdc caGjI hGdMeO ddg hMOg , Je GdcJGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe jhSa YWGjG Hf ejNGFjd YWGjG GdWHjH SfI (B1262(3g`s
(3HChdg hbajI HGSe eMeO SYjO Hf eMeO Hc EjGS GdOeTbi eDQN SfI (B1373(3g`s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdWHs